MEMBUJUK ANAK UNTUK MELAKUKAN VIDEO CALL SEX MELALUI SOSIAL MEDIA (PUTUSAN NOMOR 392/PID.SUS/2021/PN.JKTSEL): Persuad Children to Conduct Video Call Sex Through Social Media (Decision Number 392/PID.SUS/2021/PN.Jkt.Sel) - Bangun, Leony Retdalia Betri; Widiatno, Andi (AMICUS CURIAE, 2024)
Based on Decision Number 392/Pid.Sus/2021/PN Jkt, the Defendant's cell, Wawan Gunawan, requested the victim's WhatsApp number through the Hago application and persuaded the victim, who was underage, to video call sex. Based on this, is the defendant's actions in persuading children to video call sex through social media in accordance with Article 27 paragraph (1) of the ITE Law and what are the aggravating elements in the crime of persuading children to video call sex through social media. The type of research used is normative juridical, which is descriptive analytical and uses secondary data through library research. Furthermore, secondary data were analyzed qualitatively and conclusions were drawn using deductive methods. The results of this study show that the Defendant's actions in persuading children to make video calls sex through social media are in accordance with Article 27 Paragraph (1) of the ITE Law, but it is not appropriate if the sentence is only 2 years because the Defendant's actions should be more appropriate to be subject to Article 27 paragraph (1) jo Article 45 paragraph (1) jo Article 52 paragraph (1) with a sentence of 8 years in prison, because the Defendant committed a crime against a minor.